2015
DOI: 10.1007/s13412-015-0288-y
|View full text |Cite
|
Sign up to set email alerts
|

Local is not always better: the impact of climate information on values, behavior and policy support

Abstract: In the current research, we experimentally examined the effect of providing local or global information about the impacts of climate change on individuals' perceived importance of climate change and on their willingness to take action to address it, including policy support. We examined these relationships in the context of individuals' general value orientations. Our findings, from 99 US residents, suggest that different kinds of climate information (local, global, or none) interact with values vis-à-vis our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 51 publications
6
42
1
1
Order By: Relevance
“…For example, proximal information may act as a deterrent to individuals who value wider communities and the environment. Furthermore, Schoenefeld and McCauley show that empirical evidence does not support a straightforward, self‐interest‐based theorization of this issue. In fact, people with more self‐interested value orientations who received local climate information were found to disengage from climate change action and policy support, producing a ‘reactance effect.’ Thus, simply highlighting the local effects of climate change is unlikely to unequivocally stimulate action.…”
Section: Determinants Of Individual Participation In Collective Climamentioning
confidence: 98%
See 1 more Smart Citation
“…For example, proximal information may act as a deterrent to individuals who value wider communities and the environment. Furthermore, Schoenefeld and McCauley show that empirical evidence does not support a straightforward, self‐interest‐based theorization of this issue. In fact, people with more self‐interested value orientations who received local climate information were found to disengage from climate change action and policy support, producing a ‘reactance effect.’ Thus, simply highlighting the local effects of climate change is unlikely to unequivocally stimulate action.…”
Section: Determinants Of Individual Participation In Collective Climamentioning
confidence: 98%
“…Values, or ‘enduring belief[s] that a specific mode of conduct or end‐state of existence is personally or socially preferable to an opposite or converse mode of conduct or end‐state of existence,’ correlate strongly and consistently with pro‐environmental and pro‐climate behavior. As Corner et al emphasize in their detailed review, individuals with ‘self‐transcendent’ value orientations (such as caring about wider communities, or the environment) engage more in pro‐environmental behavior than people who privilege ‘self‐enhancing’ values that focus on individual gain or status . Attitudes may be defined as ‘a learned predisposition to respond in a consistently favourable or unfavourable manner with respect to a given object.’ Large‐scale meta‐analyses have shown that, in contrast to values, attitudes are less enduring and less linked with pro‐environmental behavior .…”
Section: Determinants Of Individual Participation In Collective Climamentioning
confidence: 99%
“…Out of this context, the role of values, beliefs, worldviews, identity, and meaning‐making has become one of the most prominent occupations of climate communication researchers . Among the critical takeaways from this body of work is that, first, we all hear, perceive, make sense of, and judge incoming information (be it spoken, written, visual, or sensory) through the filters of culturally transmitted values and no one can escape this influence although we can become conscious of this influence and actively probe it, if we are willing.…”
Section: The Fieldmentioning
confidence: 99%
“…Most have found that self-transcendent values positively predict support for climate policy (Cheung et al, 2014;Drews & van den Bergh, 2016;Howell & Allen, 2017;Schoenefeld & McCauley, 2016). While some such studies have used instruments designed to measure the whole spectrum of values theorised by Schwartz, several have restricted themselves to questions relating to the self-enhancement versus self-transcendence value dimension of the theory (Howell & Allen, 2017;Nilsson et al, 2004;Nordlund & Garvill, 2002;Schoenefeld & McCauley, 2016;Steg et al, 2005). Given that self-enhancement values are opposed to self-transcendent values in the Schwartz values model, most of these studies find a negative effect of self-enhancement values on support for climate policy.…”
Section: Human Valuesmentioning
confidence: 99%